Probing the mechanism of recognition of ssDNA by the Cdc13-DBD - Eldridge, Aimee M. (Oxford University Press, 2008)
The Saccharomyces cerevisiae protein Cdc13 tightly and specifically binds the conserved G-rich single-stranded overhang at telomeres and plays an essential role in telomere end-protection and length regulation. The 200 residue DNA-binding domain of Cdc13 (Cdc13-DBD) binds an 11mer single-stranded representative of the yeast telomeric sequence [Tel11, d(GTGTGGGTGTG)] with a 3 pM affinity and specificity for three bases (underlined) at the 5′ end. The structure of the Cdc13-DBD bound to Tel11 revealed a large, predominantly aromatic protein interface with several unusual features. The DNA adopts an irregular, extended structure, and the binding interface includes a long (∼30 amino acids) structured loop between strands β2-β3 (L(2–3)) of an OB-fold. To investigate the mechanism of ssDNA binding, we studied the free and bound states of Cdc13-DBD using NMR spectroscopy. Chemical shift changes indicate that the basic topology of the domain, including L(2–3), is essentially intact in the free state. Changes in slow and intermediate time scale dynamics, however, occur in L(2–3), while conformational changes distant from the DNA interface suggest an induced fit mechanism for binding in the ‘hot spot’ for binding affinity and specificity. These data point to an overall binding mechanism well adapted to the heterogeneous nature of yeast telomeres.